2013
DOI: 10.1037/a0034201
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampus, time, and memory—A retrospective analysis.

Abstract: In 1984, there was considerable evidence that the hippocampus was important for spatial learning and some evidence that it was also involved in duration discrimination. The article Hippocampus, Time, and Memory (Meck, Church, and Olton, 1984), however, was the first to isolate the effects of hippocampal damage on specific stages of temporal processing. In this review, to celebrate the 30th anniversary of Behavioral Neuroscience, we look back on factors that contributed to the long-lasting influence of this art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 222 publications
(389 reference statements)
6
62
0
1
Order By: Relevance
“…Importantly, both pre-training and post-training DH lesions produced leftward shifts in peak times, confirming previous investigations and suggesting a possible role for the DH in the cortical-striatal-based timing mechanisms [16,20,22,23,25,70]. Importantly, examination of the individual-trial performance revealed that earlier 'start' times rather than earlier 'stop' times or a combination of both could well be the reason for the observed leftward shifts of peak times.…”
Section: Discussion (A) Dorsal and Ventral Hippocampal Lesions Differsupporting
confidence: 69%
See 3 more Smart Citations
“…Importantly, both pre-training and post-training DH lesions produced leftward shifts in peak times, confirming previous investigations and suggesting a possible role for the DH in the cortical-striatal-based timing mechanisms [16,20,22,23,25,70]. Importantly, examination of the individual-trial performance revealed that earlier 'start' times rather than earlier 'stop' times or a combination of both could well be the reason for the observed leftward shifts of peak times.…”
Section: Discussion (A) Dorsal and Ventral Hippocampal Lesions Differsupporting
confidence: 69%
“…fimbria-fornix lesions or complete hippocampal cytotoxic lesions) responded earlier than the scheduled time of reinforcement in a variety of peak-interval procedures [20,68], suggesting that the hippocampus plays a role in temporal memory [25]. Hippocampal lesions also disrupt responding in differential reinforcement of low rates (DRL) schedules.…”
Section: Discussion (A) Dorsal and Ventral Hippocampal Lesions Differmentioning
confidence: 99%
See 2 more Smart Citations
“…Meck and colleagues (Allman et al, 2014;Coull et al, 2011; in press b; Lewis & Meck, 2012;MacDonald et al, 2014;Matell & Meck, 2000Meck et al, 2008Meck et al, , 2013Merchant et al, 2013;Van Rijn et al, in press) have proposed a unified timing model in which the perception and estimation of time depends on the interaction of multiple brain areas as outlined in Figure 1. These include structures that are consistently involved in temporal processing across different timing contexts, comprising a core-timing network, as well as areas that are activated in a context-dependent/sensory-specific fashion (e.g., visual cortex or cerebellum -see Chen & Zhou, 2014;Teki et al, 2012 - Fig.…”
Section: Future Directionsmentioning
confidence: 99%